Liquid-liquid equilibrium of poly(ethylene glycol) 4000+diammonium hydrogen phosphate plus water at different temperatures - Samuthira Pandian, Amaresh; Shreela, Murugesan; Iyyaswami, Regupathi; Thanapalan, Murugesan (AMER CHEMICAL SOC, 1155 16TH ST, NW, WASHINGTON, DC 20036 USA, 2008)
Abstract: Liquid-liquid equilibrium for an aqueous two-phase system containing poly(ethylene glycol) 4000 + diammonium hydrogen phosphate + water was studied at four different temperatures of (25, 30, 35, and 45) degrees C. The binodal curve was fitted to three different empirical equations relating the concentrations of PEG 4000 and diammonium hydrogen phosphate, and the coefficients were estimated for the respective temperatures for all three equations. The effective excluded volume values were obtained from the binodal model for the present system, and salting-out ability of the salt was discussed. Tie line compositions were correlated using the Othmer-Tobias and Bancroft equations, and the parameters are also reported. Further, the experimental binodal data of the poly(ethylene glycol) 4000 + diammonium hydrogen phosphate + water system were compared to poly(ethylene glycol) 6000 + diammonium hydrogen phosphate + water for (25, 35, and 45) degrees C.